Breakthrough invasive fungal infection after liver transplantation in patients on targeted antifungal prophylaxis: A prospective multicentre study. Issue 4 (3rd May 2021) - Rinaldi, Matteo; Bartoletti, Michele; Ferrarese, Alberto; Franceschini, Erica; Campoli, Caterina; Coladonato, Simona; Pascale, Renato; Tedeschi, Sara; Gatti, Milo; Cricca, Monica; Ambretti, Simone; Siniscalchi, Antonio; et al.
Abstract: Objective: To investigate the rate of and the risk factors for breakthrough‐IFI (b‐IFI) after orthotopic liver transplantation (OLT) according to the new definition proposed by Mycoses‐Study‐Group‐Education‐and‐Research‐Consortium (MSG‐ERC) and the European‐Confederation‐of‐Medical‐Mycology (ECMM). Methods: Multicenter prospective study of adult patients who underwent OLT at three Italian hospitals, from January 2015 to December 2018. Targeted antifungal prophylaxis (TAP) protocol was developed and shared among participating centers. Follow‐up was 1‐year after OLT. B‐IFI was defined as infection occurring during exposure to antifungal prophylaxis. Risk factors for b‐IFI were analyzed among patients exposed to prophylaxis by univariable analysis. Results: We enrolled 485 OLT patients. Overall compliance to TAP protocol was 64.3%, 220 patients received antifungal prophylaxis, 172 according to TAP protocol. Twenty‐nine patients were diagnosed of IFI within 1 year after OLT. Of them, 11 presented with b‐IFI within 17 (IQR 11‐33) and 16 (IQR 4‐30) days from OLT and from antifungal onset, respectively. Then out of 11 patients with b‐IFI were classified as having high risk of IFI and were receiving anti‐mould prophylaxis, nine with echinocandins and one with polyenes. Comparison of patients with and without b‐IFI showed significant differences for prior Candida colonization, need of renal replacement therapy after OLT, re‐operation, and CMV infection (whole blood CMV‐DNA >100 000 copies/mL). Although non‐significant, a higher rate of b‐IFI in patients on echinocandins was observed (8.2% vs 1.8%, P = .06). Conclusions: We observed 5% of b‐IFI among OLT patients exposed to antifungal prophylaxis. The impact of echinocandins on b‐IFI risk in this setting should be further explored.